The Role of KBIHU as a Multicultural Educational Institution in Society - Bachroni; Anggara Disuma; Slamet Firdaus; Jamali; Didin Nurul Rosidin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Multicultural-based education is very important to be implemented in all educational units. This study aims to analyze the principles of Multicultural Education that are applied in the Hajj management guidance process at KBIHU Wadi Fatimah. This study uses qualitative methods with observation, documentation and in-depth interviews. The results of the study show that as an Islamic educational institution and the guidance of pilgrims it is important to adopt the principles of multicultural Islamic Education in terms of: Equality of the rights of pilgrims without exception for all pilgrims in service, Management of development that is integral and integrated with supporting facilities; Holistic curriculum for physical and spiritual aspects; The principle of respecting differences in understanding and belief in the implementation of the pilgrimage. This finding is important because Islamic coaching institutions are quite popular in the community and have been able to succeed in government programs.